Restoration of caveolin‐1 expression suppresses growth, membrane‐type‐4 metalloproteinase expression and metastasis‐associated activities in colon cancer cells. Issue 11 (1st June 2012) - Nimri, Lili; Barak, Hossei; Graeve, Lutz; Schwartz, Betty
Abstract Caveolin‐1 (cav‐1) and flotillin‐1 are two major structural proteins associated with lipid rafts in mammalian cells. The membrane‐type matrix metalloproteinases (MT‐MMPs) are expressed at the cell surface, hydrolyze extracellular matrix, and play an important role in cancer cell migration and metastasis. Expression of cav‐1, flotillin‐1, and MT4‐MMP in lysates and lipid rafts of LS174T and HM‐7 colon cancer cells was determined. The impact of restoration of cav‐1 expression on proliferation, adhesion, motility in vitro, and growth of implanted tumors in vivo was characterized. Cav‐1 is not expressed in lipid rafts of the highly metastatic colon cancer cell line (HM‐7), but expressed in cytosolic fractions of the parental lower metastatic cell line (LS174T). In contrast, MT4‐MMP was expressed in lipid rafts of HM‐7 cells but not in LS174T cells. Overexpression of cav‐1 in HM‐7 cells down‐regulate proliferation, viability, wound closure, adhesion to laminin, invasion, and development of filopodial and lamellipodial structures in a dose‐dependent manner. Cav‐1 positive HM‐7 clones ceased to express MT4‐MMP in their lipid rafts. Comparative proteomic analyses of lipid rafts from cav‐1 positive and cav‐1 negative cells demonstrated de novo expression of flotillin‐1 only on the cells expressing cav‐1. Xenografting control cells devoid of cav‐1 in nude mice induced development of bigger tumors expressing higher levels of proliferating cell nuclear antigen as compared to mice injected with cells expressing the highest cav‐1 levels. We conclude that cav‐1 orchestrates and reorganize several proteins in lipid rafts, activities directly associated with reduced tumorigenic and metastatic ability of colon cancer cells. © 2012 Wiley Periodicals, Inc.